Improvement of Yield and Mineral Content in Two Cultivars of Vicia faba L. Through Physical and Chemical Mutagenesis and their Character Association Analysis - , Shahnawaz Khursheed; , Aamir Raina; , Samiullah Khan (Archives of Current Research International, 2016)
World is continuously facing the food insecurity and malnutrition problem. Scientists all over the world are busy in developing the latest and innovative approaches for reducing the hunger and malnutrition problem which are increasing at an alarming rate throughout the world. The current experiment was conducted to improve the yield and nutritional quality of two cultivars of faba bean viz., Vikrant and PRT-12. The seeds of two cultivars were treated with single and combined treatments of gamma rays and ethyl methanesulphonate (EMS) in M1 generation. The seeds collected from M1 plants were sown to raise the M2generation. High yielding plants from lower treatments of gamma rays, EMS and their combinations were analyzed for yield and different mineral elements like zinc, iron and manganese using atomic absorption spectrophotometer (AAS). Both cultivars showed significant increase in yield and mineral content. Variety Vikrant showed more increase in yield and mineral content towards mutagen treatments than PRT-12. This approach can be utilized on other plants to improve the yield and nutritional quality of plants. This will overcome the increasing rate of hunger and malnutrition problem throughout the world.